A Descriptive Study On Teaching Speaking Method To The Seventh Year Student Of SMP Negeri 3 Baturetno - Sari, Dwi Wulan, Drs. Djoko Srijono, M.Hum, Siti Fatimah, S.Pd, M.Hum (2013)
This research paper is intended to describe " A Descriptive Study on Teaching Speaking Method to The Seventh Year Student of SMP Negeri 3 Baturetno". Speaking is one of the fundamental essential skills to master in learning a foreign language. Not only bearing a highly communicative value, but also regarding as the parameter of one's proficiency in a foreign language. There are five components in speaking skill; they are pronunciation, grammar, vocabulary, fluency, and comprehension. The KTSP curriculum has been a base of teaching speaking, where the students are expected to master not only one skill, but all skills of English namely listening, reading, speaking and writing. The writer focuses the English teaching-learning process, on the seven year students. The purpose of this research is to know the implementation of teaching speaking method to the seventh year student of SMP Negeri 3 Baturetno. The data are taken from all elements of teaching-learning process committed by the teacher and the students and other sources such as books, students practice, lesson plan, etc. The method of collecting data is descriptive method by employing interview, documentation and observation. This research is descriptive qualitative which does not include any calculation or statistic procedure. In this research paper she describes the methods are used by teacher in teaching speaking, the strengths and weaknesses of the methods used by teachers in teaching speaking, and the problems faced by teacher and students in speaking class. The subject of the study is limited on the seventh year students of SMP Negeri 3 Baturetno 2013/2014 academic year. She took class that consists of 30 students. The result of the research is the implementation of teaching speaking is divided into two main sections; (1) Teacher activity consists of all preparations of the teacher in teaching speaking, and (2) The elements of speaking course. The problems of teaching speaking are about the less of the materials that can influence teaching learning process. The urgent problems faced by the teacher are less of the materials. Because many kinds of the materials must be presented to the students. The Problems Faced by Students: (1) Students Inhibition.(2) Nothing to say. (3) Low participation.(4) Mother-tongue use. (5) The students have problem with grammar. Based on the data the portion of teaching speaking is enough because the speaking activity will be integrated with other English skills.